John Quincy Adams: A Public Life, A Private Life - Nagel, C. Paul 1970- (Cambridge: A. Knopf, Inc., 1999)
A biography of the man who served as foreign minister, senator, and sixth president of the United States.
Includes index.
Keywords: 1767-1848 -- Juvenile literature; Adams, John Quincy, -- 1767-1848.; Presidents -- United States -- Biography -- Juvenile literature; Presidents